Diagnostic accuracy of ultrasonography for hand bony fractures in paediatric patients. - Neri, Elena; Barbi, Egidio; Rabach, Ingrid; Zanchi, Chiara; Norbedo, Stefania; Ronfani, Luca; Guastalla, Veronica; Ventura, Alessandro; Guastalla, Pierpaolo (Arch Dis Child, 2014)
OBJECTIVE: Hand fractures are common in childhood, and radiography is the standard diagnostic procedure. US has been used to evaluate bone injuries, mainly in adults for long-bone trauma; there are only a few studies about hand fractures in children. The purpose of this study was to evaluate and confirm the safety and applicability of the US diagnostic procedure in comparison to X-ray diagnosis. STUDY DESIGN: This cross-sectional study involved a convenience sample of young patients (between 2 and 17 years old) who were taken to the emergency department due to hand trauma. After clinical assessment, patients with a suspected hand fracture first underwent X-ray, and subsequently US examination by two different operators; a radiologist experienced in US and a trained emergency physician in "double-blind" fashion. US and radiographic findings were then compared, and sensitivity as well as specificity was calculated. RESULTS: A total of 204 patients were enrolled in the study. Seventy-nine fractures of phalanges or metacarpals were detected by standard radiography. When US imaging was performed by an expert radiologist, 72 fractures were detected with sensitivity and a specificity of 91.1% and 97.6%, respectively. Sensitivity and specificity were found to be (respectively) 91.5% and 96.8% when US was performed by the ED physicians. CONCLUSIONS: US imaging showed excellent sensitivity and specificity results in the diagnosis of hand fractures in children. The study also showed a great agreement between the results of the US carried out by the senior radiologist and those carried out by the paediatric emergency physician, suggesting that US can be performed by an ED physician, allowing a rapid and accurate evaluation in ED and could become the first diagnostic approach whenever a hand fracture is suspected.
Keywords: Adolescent; Child; Child, Preschool; Cross-Sectional Studies; Double-Blind Method; Emergency Service, Hospital; Female; Fractures, Bone; Hand Bones; Humans; Italy; Male; Sensitivity and Specificity

A precordial rub in a boy with a severe attack of ulcerative colitis. - Badina, Laura; Ferrara, Giovanna; Guastalla, Pierpaolo; Barbi, Egidio (Pediatr Emerg Care, 2014)
A case of a pneumomediastinum mimicking a pericarditis in a boy with an occult perforation due to ulcerative colitis is reported. Pneumomediastinum is a rare complication of severe attacks of ulcerative colitis, with or without the previous development of a toxic megacolon, that should be considered in the differential diagnosis.
Keywords: Adolescent; Colitis, Ulcerative; Diagnosis, Differential; Humans; Intestinal Perforation; Male; Mediastinal Emphysema; Pericarditis; Radiography, Thoracic

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical